Chronicles of Cell Death Foretold: Specificities in the Mechanism of Disposal - Hughes, Lindsey D.; Bosurgi, Lidia; Ghosh, Sourav; Rothlin, Carla V. (Frontiers in Immunology, 2017)
Massive turnover of cells occurs through apoptosis during the constant remodeling of our tissues at homeostasis, from the shedding of cells at exposed barrier surfaces to the elimination of autoreactive lymphocytes. However, a surge of apoptotic cells also accompanies tissue damage, infection, and inflammation. A salient feature of apoptosis in either scenario is the exposure of phosphatidylserine on the outer leaflet of the plasma membrane. In response to this cue, a range of phagocytes are charged with the sizeable task of engulfing apoptotic bodies and disposing of the billions of cells that perish each day. The presence of apoptotic cells in the remarkably distinct immunological settings described above, therefore, raises the question of how phagocytes are able to coordinate appropriate responses to apoptotic cells— from their silent removal to the production of growth factors or tissue repair molecules— following such a ubiquitous signal as phosphatidylserine exposure. Here we consider several emergent properties of phagocytes and apoptotic cell clearance that may facilitate specification among this suite of potential responses.